Biological fundamentals, operational tools, and innovation in plant quarantine - Marques, Abi Soares dos Anjos; Lopes-da-Silva, Marcelo; Gonzaga, Vilmar; Fernandes, Fernanda Rausch; Benito, Norton Polo; Veiga, Renato Ferraz de Arruda (Pesquisa Agropecuaria Brasileira, 2016)
The demand toward food and nutritional security delimitates models for agricultural intensification, in which yield loss prevention is essential. The globalized agriculture scenario, the increase of trade routes, and the displacement of people and products maximize the potential of nondeliberate pest introductions in undamaged areas, endangering the production systems. Plant quarantine is presented as a measure to control plant product movement, in order to limit the dispersal of agricultural pests. Surveillance advocates the anticipation and recognizes the threat, focusing on the accuracy and efficiency of the diagnosis, on the consolidation of methods of pest risk analysis, and on the evolution of operational tools. Responses to the challenges posed to agriculture security are expected, considering the appropriation of new technologies, enhancement of inspectorate structures, and a strong, innovative capacity. This work approaches the historical aspects related to quarantine actions, legal framework, influence of international trade, analytical tools, innovation perspectives, and infrastructure qualification. The objective of this work is to contextualize the risk importance of introducing new pests, faced with a thriving agriculture and the intensification of commercial interchange. It also analyses the challenges to plant quarantine actions, while it aligns the biological grounding on which the phytosanitary regulation should be sustained, in order to subside the formulation of legal security measures.